2005
DOI: 10.1093/jac/dki323
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ceftriaxone, vancomycin and rifampicin alone and combined in an experimental model of meningitis caused by highly cephalosporin-resistant Streptococcus pneumoniae ATCC 51916

Abstract: Ceftriaxone plus vancomycin, and vancomycin plus rifampicin appeared to be effective in the therapy of experimental pneumococcal meningitis caused by highly cephalosporin-resistant strains such as ATCC 51916. Our results provide an experimental basis for using these combinations as empirical therapy for pneumococcal meningitis, regardless of the degree of cephalosporin resistance of the causative strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 9 publications
1
8
0
1
Order By: Relevance
“…This is in agreement with the in vivo study by Ribes et al [26], where rifampicin achieved excellent bactericidal effects in CSF at concentrations of ≥ 3.7 × MIC, whereas in broth, only bacteriostatic effects were observed. The in vivo reduction of -4.25 Δlog 10 CFU/ml observed with S. pneumoniae at the mentioned concentration range of approximately 3-13 times the MIC at 24 h was similar to the in vitro reduction of -3 to -4 Δlog 10 CFU/ml in CSF at 24 h with S. aureus at rifampicin concentrations ranging from 2 to 8 times the MIC [13] .…”
Section: Comparison In Vitro Vs In Vivo and Conclusionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with the in vivo study by Ribes et al [26], where rifampicin achieved excellent bactericidal effects in CSF at concentrations of ≥ 3.7 × MIC, whereas in broth, only bacteriostatic effects were observed. The in vivo reduction of -4.25 Δlog 10 CFU/ml observed with S. pneumoniae at the mentioned concentration range of approximately 3-13 times the MIC at 24 h was similar to the in vitro reduction of -3 to -4 Δlog 10 CFU/ml in CSF at 24 h with S. aureus at rifampicin concentrations ranging from 2 to 8 times the MIC [13] .…”
Section: Comparison In Vitro Vs In Vivo and Conclusionsupporting
confidence: 93%
“…In vivo Ribes et al [26] jections at a dosage of 15 mg/kg and performed a concomitant static in vitro time-kill study in an unspecified medium. For unclear reasons, different time points (6 h in vitro and 24 h in vivo) were used for the quantification of antibacterial effects, perturbing the comparability of the data.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Rifampin combination therapy has been used for S. pneumoniae infections, especially meningitis caused by penicillin-resistant strains (penicillin-resistant S. pneumoniae [PRSP]) (56,211,236).…”
Section: Other Diseasesmentioning
confidence: 99%
“…The in vitro data for the vancomycin-rifampin combination therapy for treatment of S. pneumoniae infection using time-kill studies again showed indifference, similarly to S. aureus (94). Despite data suggesting that rifampin has poor penetration into the brain, animal studies have had mixed results (56,179,211,236). Using a rabbit model, Nau et al found that rifampin was significantly less active against S. pneumoniae in the CSF than ceftriaxone, with paradoxically less efficacy at higher doses of rifampin (179).…”
Section: Other Diseasesmentioning
confidence: 99%
See 1 more Smart Citation